GDP solera: The ideal vintage mix - Martín Almuzara; Dante Amengual; Gabriele Fiorentini; Enrique Sentana (Federal Reserve Bank of New York, 2022)
We exploit the information in the successive vintages of gross domestic expenditure (GDE) and gross domestic income (GDI) from the current comprehensive revision to obtain an improved, timely measure of U.S. aggregate output by exploiting cointegration between the different measures and taking their monthly release calendar seriously. We also combine all existing overlapping comprehensive revisions to achieve further improvements. We pay particular attention to the Great Recession and the pandemic, which, despite producing dramatic fluctuations, does not generate noticeable revisions in previous growth rates. The estimated parameters of our dynamic state-space model suggest that comprehensive revisions have not changed the long-run growth rate of U.S. GDP.
Keywords: E01; C32; 330; cointegration; comprehensive revisions; signal extractions; U.S. aggregate output; vintages